2023
DOI: 10.1021/acsami.2c18716
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights on the Metal–Support Interactions of Pd/ZrO2 Catalysts on CH4 Oxidation

Abstract: With the environmental harm of unburnt CH4 in natural gas vehicle exhaust, oxidizing CH4 to CO2 over catalysts at low temperatures becomes an exigent issue. Supported Pd catalysts possess higher CH4 activity than other noble metal catalysts. A series of Pd/ZrO2 catalysts were synthesized to research the potential relationship among Pd particle morphology, electron transfer, CH4 oxidation mechanism, and catalytic activity. Characterizations show that the ratio of PdO x facets to edge/corner sites on four catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…7,60 This signal gradually diminished as the reaction temperature increased to 450 °C, accompanied by the appearance of adsorbed CO 2 (2355 and 2382 cm −1 ). 25,61 Methane oxidation was enhanced on the PdIrx/S-1 samples, as evidenced by the lower temperatures for CO 2 formation observed on PdIr 0.1 /S-1 (400 °C) and PdIr 0.25 /S-1 (350 °C) (Figure 4f and Figure S22). This result was consistent with the CH 4 -TPR experiment as well as their catalytic performance in methane combustion.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…7,60 This signal gradually diminished as the reaction temperature increased to 450 °C, accompanied by the appearance of adsorbed CO 2 (2355 and 2382 cm −1 ). 25,61 Methane oxidation was enhanced on the PdIrx/S-1 samples, as evidenced by the lower temperatures for CO 2 formation observed on PdIr 0.1 /S-1 (400 °C) and PdIr 0.25 /S-1 (350 °C) (Figure 4f and Figure S22). This result was consistent with the CH 4 -TPR experiment as well as their catalytic performance in methane combustion.…”
Section: Resultsmentioning
confidence: 93%
“…In situ DRIFTS experiments were conducted to investigate the reactive intermediates of methane oxidation on these PdIr x /S-1 catalysts. During steady-state methane oxidation on Pd/S-1 (Figure S21), the C–H stretching signal (3016 cm –1 ) of CH 4 species was observed at 300 °C. , This signal gradually diminished as the reaction temperature increased to 450 °C, accompanied by the appearance of adsorbed CO 2 (2355 and 2382 cm –1 ). , Methane oxidation was enhanced on the PdIr x /S-1 samples, as evidenced by the lower temperatures for CO 2 formation observed on PdIr 0.1 /S-1 (400 °C) and PdIr 0.25 /S-1 (350 °C) (Figure f and Figure S22). This result was consistent with the CH 4 -TPR experiment as well as their catalytic performance in methane combustion.…”
Section: Resultsmentioning
confidence: 96%
“…Figure (a) shows the Pd 3d XPS spectra of the two catalysts. For 0.5Pd/TiO 2 catalyst, there are two XPS peaks at about 337.1 and 342.4 eV, which can be assigned to Pd 2+ . , Compared with 0.5Pd/TiO 2 , the peak position over 0.5Pd/SiO 2 –TiO 2 (C) was shifted to lower binding energy by ∼0.5 eV, which suggests a stronger interaction existed between Pd and SiO 2 –TiO 2 (C). , The XPS speaks for 0.5Pd/SiO 2 –TiO 2 (C) can be divided into three separate peaks at 335.5, 336.6, and 341.8 eV, which are ascribed to Pd 0 and Pd 2+ , respectively . The Pd 0 /(Pd 0 + Pd 2+ ) ratio over 0.5Pd/SiO 2 –TiO 2 (C) was about 6.2%.…”
Section: Resultsmentioning
confidence: 99%
“…6 At present, noble metal catalysts show good catalytic performance for CH 4 oxidation. 7,8 Park et al 9 synthesized a Pd/Pt catalyst for CH 4 oxidation. The results showed that the interaction of Pd and Pt easily yields active PdO-Pt counter-sites to promote CH 4 oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase CO 2 was adsorbed on terminal-type oxygen MnO to form a surface monodentate carbonate (v as (CO 5 and 6). Mn-□-Mn might be produced because the O 2 decomposition rate to Mn-O-Mn following eqn (8) was lower than the Mn-O-Mn consumption rate (eqn ( 4)). The Mn-O-Mn regeneration experiments in an O 2 /Ar atmosphere (Table S1 †) were conducted.…”
mentioning
confidence: 99%